Experimental reconstitution of chronic ER stress in the liver reveals feedback suppression of BiP mRNA expression - Javier A Gomez; D Thomas Rutkowski (eLife, 2016)
Endoplasmic reticulum (ER) stress is implicated in many chronic diseases, but very little is known about how the unfolded protein response (UPR) responds to persistent ER stress in vivo. Here, we experimentally reconstituted chronic ER stress in the mouse liver, using repeated injection of a low dose of the ER stressor tunicamycin. Paradoxically, this treatment led to feedback-mediated suppression of a select group of mRNAs, including those encoding the ER chaperones BiP and GRP94. This suppression was due to both silencing of the ATF6α pathway of UPR-dependent transcription and enhancement of mRNA degradation, possibly via regulated IRE1-dependent decay (RIDD). The suppression of mRNA encoding BiP was phenocopied by ectopic overexpression of BiP protein, and was also observed in obese mice. Our findings suggest that persistent cycles of UPR activation and deactivation create an altered, quasi-stable setpoint for UPR-dependent transcriptional regulation—an outcome that could be relevant to conditions such as metabolic syndrome.